The lives of extraction : identities, communities, and the politics of place - Calvão, Filipa Urbano; Archer, Matthew; Benya, Asanda (International development policy ;, 2024)
"The frontiers of extraction are expanding rapidly, driven by a growing demand for minerals and metals that is often motivated by sustainability considerations. Two volumes of International Development Policy are dedicated to the paradoxes and futures of green extractivism, with analyses of experiences from five continents. In this, the first of these two volumes, 16 authors offer a critical and nuanced understanding of the social, cultural and political dimensions of extraction. The experiences of communities, indigenous peoples and workers in extractive contexts are deeply shaped by narratives, imaginaries and the complexity of social contexts. These dimensions are crucial to making extraction possible and to sustaining its expansion, but also to identifying possibilities for resistance, and to paving the way for alternative, post-extractive economies. This volume is accompanied by IDP 16, The Afterlives of Extraction: Alternatives and Sustainable Futures"--